A cell type‐specific view on the translation of mRNAs from ROS‐responsive genes upon paraquat treatment of Arabidopsis thaliana leaves. (2nd June 2014) - BENINA, MARIA; RIBEIRO, DIMAS MENDES; GECHEV, TSANKO S.; MUELLER‐ROEBER, BERND; SCHIPPERS, JOS H. M.
Abstract Oxidative stress causes dramatic changes in the expression levels of many genes. The formation of a functional protein through successful mRNA translation is central to a coordinated cellular response. To what extent the response towards reactive oxygen species (ROS) is regulated at the translational level is poorly understood. Here we analysed leaf‐ and tissue‐specific translatomes using a set of transgenic Arabidopsis thaliana lines expressing a FLAG‐tagged ribosomal protein to immunopurify polysome‐bound mRNAs before and after oxidative stress. We determined transcript levels of 171 ROS‐responsive genes upon paraquat treatment, which causes formation of superoxide radicals, at the whole‐organ level. Furthermore, the translation of mRNAs was determined for five cell types: mesophyll, bundle sheath, phloem companion, epidermal and guard cells. Mesophyll and bundle sheath cells showed the strongest response to paraquat treatment. Interestingly, several ROS‐responsive transcription factors displayed cell type‐specific translation patterns, while others were translated in all cell types. In part, cell type‐specific translation could be explained by the length of the 5′‐untranslated region (5′‐UTR) and the presence of upstream open reading frames (uORFs). Our analysis reveals insights into the translational regulation of ROS‐responsive genes, which is important to understanding cell‐specific responses and functions during oxidative stress.